Unraveling Reticulate Evolution in Opuntia (Cactaceae) From Southern Mexico - Granados-Aguilar, Xochitl; Granados Mendoza, Carolina; Cervantes, Cristian Rafael; Montes, José Rubén; Arias, Salvador (Frontiers in Plant Science, 2021)
The process of hybridization occurs in approximately 40% of vascular plants, and this exchange of genetic material between non-conspecific individuals occurs unequally among plant lineages, being more frequent in certain groups such as Opuntia (Cactaceae). This genus is known for multiple taxonomic controversies due to widespread polyploidy and probable hybrid origin of several of its species. Southern Mexico species of this genus have been poorly studied despite their great diversity in regions such as the Tehuacán-Cuicatlán Valley which contains around 12% of recognized Mexico’s native Opuntia species. In this work, we focus on testing the hybrid status of two putative hybrids from this region, Opuntia tehuacana and Opuntia pilifera, and estimate if hybridization occurs among sampled southern opuntias using two newly identified nuclear intron markers to construct phylogenetic networks with HyDe and Dsuite and perform invariant analysis under the coalescent model with HyDe and Dsuite. For the test of hybrid origin in O. tehuacana, our results could not recover hybridization as proposed in the literature, but we found introgression into O. tehuacana individuals involving O. decumbens and O. huajuapensis. Regarding O. pilifera, we identified O. decumbens as probable parental species, supported by our analysis, which sustains the previous hybridization hypothesis between Nopalea and Basilares clades. Finally, we suggest new hybridization and introgression cases among southern Mexican species involving O. tehuantepecana and O. depressa as parental species of O. velutina and O. decumbens.